Le cheval de course en Île-de-France, une présence architecturale et paysagère - Sophie Cueille (In Situ)
Fontainebleau, the plain of Sablons, the wood of Vincennes are at the end of the 18th century hangouts for the first amateurs of Horse-races. " Elegant and refined diversion ", this practice, coming of Great Britain is going to become little by little a real institution among which the frame and the rules are formalized by the Jockey club during 1830s. Stud farms, training centers, stables and number of racecourses are built in the whole of the circumference of the capital offering a big diversity in the stylistic choices and the implemented. Image of a sports practice but also architecture of leisure, these buildings deserve the attention. For some already destroyed, for the others on the way to the being, there is still time to pay attention on these real heritage. From the existing files within the various patrimonial departments of the Ministry of Culture and the Regional council of Île-de-France, this presentation suggests making a first balance sheet.